Performance of wheat (Triticum aestivum) varieties under different thermal regimes and N-levels - GUPTA, VIKAS; GUPTA, MEENAKSHI; BHARAT, RAJEEV; SINGH, MAHENDER; SHARMA, B C (The Indian Journal of Agricultural Sciences, 2020)
Present study was carried out during rabi 2015-16 and 2016-17 at SKUAST-Jammu to evaluate the performance of different varieties of wheat (Triticum aestivum L.) under thermal regimes and N-levels in terms of agrometerological indices like accumulated growing degree days (AGDD), heliothermal units (AHTU), photothermal units (APTU), heat use efficiencies (HUE) of grain and biological yields. The treatments comprised of three wheat varieties (HD 2967, RSP 561 and WH 1105) planted in three sowing environments 25th October (early), 14th November and 4th December with three levels of nitrogen (100, 125 and 150 kg/ha) in split split plot design. Among the varieties, WH 1105 recorded significantly higher AGDD, AHTU, APTU and HUE than HD 2967 and RSP 561. Early sowing (25th October) of wheat also recorded higher AGDD, HTU, PTU and HUE values and grain and biological yield HUE than normal (14th November) and late sowing (4th December) environments. Delayed planting resulted in the reduction of accumulation of thermal indices along with HUE. Fifty kg higher nitrogen (150 kg/ha) than recommended dose (100 kg/ha) exhibited higher agrometerological indices values along with higher HUEs. The relationship between grain and biological yield with AGDD and HUE was highly significant during both the years under experimentation.